A single-image retrieval method for edge illumination X-ray phase-contrast imaging: Application and noise analysis. Issue 12 (December 2016) - Diémoz, Paul C.; Vittoria, Fabio A.; Hagen, Charlotte K.; Endrizzi, Marco; Coan, Paola; Bravin, Alberto; Wagner, Ulrich H.; Rau, Christoph; Robinson, Ian K.; Olivo, Alessandro
Highlights: Edge illumination is a promising X-ray phase-contrast imaging technique. Phase retrieval usually requires the acquisition and processing of two images. A single-image retrieval algorithm for edge illumination is proposed. This greatly simplifies image acquisition and reduces data collection time. Abstract: Purpose: Edge illumination (EI) X-ray phase-contrast imaging (XPCI) has been under development at University College London in recent years, and has shown great potential for both laboratory and synchrotron applications. In this work, we propose a new acquisition and processing scheme. Contrary to existing retrieval methods for EI, which require as input two images acquired in different setup configurations, the proposed approach can retrieve an approximate map of the X-ray phase from a single image, thus significantly simplifying the acquisition procedure and reducing data collection times. Methods: The retrieval method is analytically derived, based on the assumption of a quasi-homogeneous object, i.e. an object featuring a constant ratio between refractive index and absorption coefficient. The noise properties of the input and retrieved images are also theoretically analyzed under the developed formalism. The method is applied to experimental synchrotron images of a biological object. Results: The experimental results show that the method can provide high-quality images, where the "edge" signal typical of XPCI images is transformed to an "area" contrast that enables an easier interpretation of the sample geometry. Moreover, the retrieved images confirm that the method is highly stable against noise. Conclusions: We anticipate that the developed approach will become the method of choice for a variety of applications of EI XPCI, thanks to its ability to simplify the acquisition procedure and reduce acquisitions time and dose to the sample. Future work will focus on the adaptation of the method to computed tomography and to polychromatic radiation from X-ray tubes.